Revisiting the environmental knowledge-attitude-intention relationship The case of a community adjacent to the La Mesa Watershed, Metro Manila. Proceedings of the 1st National Conference on Human Ecology, Los Baños, Laguna - Mendoza, M. E. T. (Compendium of Human Ecology Researches in the Philippines, 2003)
The study investigated the relationship between and among knowledge, attitude and behavioral intentions (KAI) of constituents of Amparo Subdivision, a community adjacent to the La Mesa Watershed regarding the protection of the Watershed. It also examined the association between selected socio-economic and demographic factors, and the KAI and behavior of the respondents toward the protection of the La Mesa Watershed. The factor analysis of the knowledge items yielded five significant underlying factors/dimensions, while the attitude items yielded four factors/dimensions. The intention items, on the other hand, clustered under 3 dimensions. The respondents generally have positive beliefs and highly favorable attitudes toward the protection of the La Mesa Watershed. They also indicated positive action-tendencies toward the protection of the Watershed. The inter-item correlation of the KAI showed a linear association between knowledge, attitude and intentions. Age, gender, civil status, religion, and years of stay in the place of residence, educational attainment, occupation and monthly income were seen as associated with respondents' KAI.